2014
DOI: 10.1177/1534735414541962
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Exercise and Lifestyle Intervention Increases Leisure-Time Activity in Breast Cancer Patients

Abstract: This integrated intervention may produce lifestyle changes in breast cancer patients and survivors using the teachable moment to increase their leisure-time physical activity and, thereby, their QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…8-11 However, only 30% to 47% of breast cancer survivors adhere to these exercise recommendations. 12 According to previous research and the study presented here, aerobic exercise, strengthening exercises, and body mind exercises have an important impact on the adverse effects of cancer survivors. 13…”
Section: Introductionmentioning
confidence: 57%
“…8-11 However, only 30% to 47% of breast cancer survivors adhere to these exercise recommendations. 12 According to previous research and the study presented here, aerobic exercise, strengthening exercises, and body mind exercises have an important impact on the adverse effects of cancer survivors. 13…”
Section: Introductionmentioning
confidence: 57%
“…It is only in the last 10 years that exercise has been recognized as an adjuvant therapy following breast cancer diagnosis. Several original papers and reviews have shown that exercise is a well‐tolerated and safe adjunct therapy during and after cancer treatment and results in improvements in physical functioning, quality of life and cancer‐related fatigue in several cancer survivor groups. Further, a recent review concluded that increasing physical activity in breast cancer treatment and survivorship has minimal to no side effects or negative consequences at any dose, type or timing (adjuvant vs. post‐adjuvant period) studied .…”
Section: Exercise May Reduce Leptin In Breast Cancermentioning
confidence: 99%
“…Breast cancer survivors report negative side effects (e.g., fatigue and hot flashes) and lack knowledge and confidence regarding safety of physical activity (Pekmezi et al, 2012), all of which are possible contributors to the reported 30%–47% of the BCS population not achieving the recommended daily activity guidelines (Casla et al, 2014). A chronic low‐grade inflammatory state has also been suggested to impact physical activity behaviors and sensations of fatigue and is also known to alter thermoregulatory control.…”
Section: Discussionmentioning
confidence: 99%